Inside the Japanese company - Graham, Fiona (Fiona Caroline) (RoutledgeCurzon, 2003)
Based on extensive original research this work explores the attitudes of Japanese employees towards their work, their company and on related issues, and finds they are much more complicated than those portrayed by Western stereotypes.